Naloxone‐associated pulmonary edema in a 3‐year‐old with opioid overdose - Sarah Grout; Madhuri Dave; Roxanna Lefort (Journal of the American College of Emergency Physicians Open)
Abstract Background Annually, close to 5000 children under age 6 years are treated in emergency departments or admitted for care due to opioid exposures. Naloxone is effectively used to treat opioid overdose in both children and adults. Non‐cardiogenic pulmonary edema is a rare but serious adverse effect of naloxone administration that has been reported in adults. Case Report We present the case of a 3‐year‐old male with suspected opioid overdose who developed acute hypoxia due to pulmonary edema after administration of naloxone following a likely prolonged downtime. Why Should an Emergency Physician Be Aware of This? The copious fluid in the airway made for difficult intubation at a pediatric tertiary care center. Given the incidence of opioid exposures in children, clinicians should be aware of this rare, but dangerous adverse effect of naloxone and consider airway precautions and pediatric critical care availability early in the presentation.